Some unremembered chemists: Francis Brian Shorland, OBE, PhD, DSc (L’pool), Hon. DSc(VUW), FRSNZ (1909-1999) - Halton, Brian (New Zealand Science Review, 2019)
Francis Brian Shorland (known as Brian) was born on 14 July 1909 in Island Bay, Wellington, New Zealand. His father John Olive Shorland (1864–1946) had been a long-distance cycling racer in the South Island and subsequently owned and operated a cycle shop in Cuba Street in Wellington. However, John’s career was as diverse as it was engaging. It encompassed building, architecture, furniture and three years as a City Councillor (1917–1920).